A qualitative analysis of online misinformation and conspiracy theories in psoriasis. (1st May 2022) - Roche, D.; Murphy, M.; O'Connor, C.
Summary: Psoriasis is a chronic, hereditary disease with a complex immunopathogenesis, rendering it susceptible to misinformation. Misinformation related to psoriasis can have negative effects both on the public perception of psoriasis and on patients' knowledge of psoriasis. To characterize misinformation related to psoriasis available online, we performed a formal literature review via PubMed and a thematic review via Google. Key themes of misinformation included 'victim‐blaming' (hygiene), 'vector' (contagion), 'vaccination', 'vilification' of conventional therapy, 'validation' of natural treatment and diet, 'veneration' of cures and 'vocalization' from celebrities. Misinformation related to psoriasis is pervasive on social media and other websites. Dermatologists, as patient advocates, should be aware of the content of misinformation available online and combat misleading health information to optimize health outcomes for patients with psoriasis. Abstract : Psoriasis is a chronic, hereditary disease with a complex immunopathogenesis rendering it susceptible to misinformation. Key themes of misinformation that were identified included 'victim‐blaming' (hygiene), 'vector' (contagion), 'vaccination', 'vilification' of conventional therapy, 'validation' of natural treatment and diet, 'veneration' of cures, and 'vocalization' from celebrities. Dermatologists, as patient advocates, should be aware of the content of misinformation available online and combat misleading health information to optimize health outcomes for patients with psoriasis.